MLAR:large-scale network alias resolution for IP geolocation - Fuxiang YUAN; Fenlin LIU; Chong LIU; Yan LIU; Xiangyang LUO (网络与信息安全学报)
In order to accurately and efficiently perform alias resolution on interface IP and support IP geolocation,a large-scale network alias resolution algorithm (MLAR) was proposed.Based on the statistical differences in delays,paths,Whois,etc.between alias IP and non-alias IP,before resolution,filtering rules were designed to exclude a large number of IPs that can not be aliases and improve efficiency of resolution,alias resolution was transformed into classification,and four novel features such as delay similarity,path similarity,etc.were constructed for the classification of possible alias IP and non-alias IP after filtering.Experiments based on millions of samples from CAIDA show that compared with RadarGun,MIDAR,and TreeNET,the accuracy is improved by 15.8%,4.8%,5.7%,the time consumption can be reduced by up to 77.8%,65.3%,and 55.2%,when the proposed algorithm is applied to IP geolocation,the failure rates of the three typical geolocation methods such as SLG,LENCR,and PoPG are reduced by about 65.5%,64.1%,and 58.1%.